Dye-stimulated control of conducting polypyrrole morphology. Issue 81 (6th November 2017) - Valtera, Stanislav; Prokeš, Jan; Kopecká, Jitka; Vrňata, Martin; Trchová, Miroslava; Varga, Martin; Stejskal, Jaroslav; Kopecký, Dušan
Abstract : Three azo dyes bearing hydrophilic functional groups at different positions on a hydrophobic naphthylphenyldiazene skeleton were used as structure-guiding agents in the synthesis of highly organised supramolecular structures of PPy in aqueous media. Abstract : Azo dyes represent important structure-guiding agents which exhibit non-covalent interactions of various types (ionic and hydrogen bonding, π–π stacking, hydrophobic interactions, etc. ) allowing for their self-assembly in aqueous solutions and the subsequent formation of seeds or templates for the preparation of supramolecular structures of conducting polymers, especially polypyrrole (PPy). Three azo dyes (Acid Red 1, Orange G and Sunset Yellow FCF) bearing hydrophilic functional groups, with mutually different positions on a hydrophobic naphthylphenyldiazene skeleton, were used as structure-guiding agents in the synthesis of highly organized supramolecular structures of PPy in aqueous media. The synthesized polymers were studied by scanning electron microscopy, energy dispersive X-ray, and Fourier-transform infrared and Raman spectroscopies. Measurement of the conductivity revealed a moderate value of conductivity (around units of S cm −1 ) and reduced stability indicated by relatively fast conductivity decay. Infrared spectroscopy indicated a lower doping level of all PPy prepared in the presence of tested dyes compared to that of standard globular PPy. In contrast, Raman spectroscopy, which is a surface-sensitive method, indicated a slightly higher protonation level compared to that of standard globular PPy or nanotubular PPy synthesized in the presence of the well-known structure-guiding agent methyl orange. This discrepancy in the obtained doping levels is discussed and some consequences between the doping level of PPy and its conductivity are also pointed out.